多自由度连杆机构的仿真与示教 - 蒯苏苏; 房义军; 吴伟光 (Jixie chuandong)
The diversity of the five-bar linkage mechanism curve is analyzed and synthesized,conditions of the five-bar mechanism with double crank conditions are revealed and determined.Using the computer,five-bar linkage with double crank mechanism,with a sliding pair five-bar linkage mechanism and with a guide block of five-bar linkage mechanism are simulated.Five-bar linkage mechanism would be controlled by MCU.Setting four function teaching actions is completed.According to the mathematical formula of five-bar linkage mechanism,multi-freedom linkage mechanism is programmed and tracing path teaching is carried out.At the same time,in the design of multi-freedom mechanical system,research basis of realizing and reliable Robust movement method is provided.